ANALYSIS OF THE RISK OF SILK TOFU PRODUCTION IN SMALL ENTERPRISE - Syamsiah, Yuliatin; Ahmad Kurniawan (Tekmapro, 2023)
Silk tofu, a unique variant of tofu packaged in thin silk sheets that provides a significantly different texture and appearance, is the subject of this research. The study aims to investigate its nutritional value, sensory attributes, and market potential. MKM Silk Tofu 57 is a prominent producer of silk tofu located in Sidoarjo, specifically at jl. Beciro No.9, Beciro, Jumputrejo, Kec. Sukodono, Sidoarjo Regency. Throughout the production process, MKM Silk Tofu 57 faces numerous risks. Hence, a risk analysis is imperative to identify optimal solutions to reduce or eliminate these arising risks. This study delves into the risks encountered by MKM Silk Tofu 57 and proposes improvements to mitigate these risks. Utilizing qualitative data, such as the company's history, and quantitative data, including numerical figures, the research employed the Failure Mode and Effects Analysis (FMEA) method to assess the risks. The results of the risk assessment, based on the Risk Priority Number ( RPN) calculations, identified the highest risk as the potential destruction of tofu during packaging, with an RPN value of 72. Risk management will be executed through the Service Quality method, encompassing five attribute methods: reliability, responsiveness, tangibility, assurance, and empathy .An observation conducted during this study yielded data and conclusions indicating the lowest satisfaction level in the assurance aspect. This signifies a lower level of accountability applied in the service provided by the silk tofu establishment, suggesting a need for enhancement in this area.